PERTUMBUHAN DAN HASIL PANEN PADI SRI (SYSTEM OF RICE INTENSIFICATION) - MENAKAADNYANA, GEDE (Agrotrop : Journal on Agriculture Science; Vol 1 No 2 (2011))
Growth and Yield of Paddy SRI (system of rice intensification). The study was conducted with the aim to conserve irrigation water use, maintaining soil health so as to support the growth of roots and the top of the rice plants become better and grain yield can be improved. The trials of SRI paddy cultivation techniques performed in the dry season planting season (MT April-May 2005) at the project site groundwater Jembrana area of 2.0 ha is in Subak Pangkung Liplip. The study results showed that the reduction in the amount of irrigation water does not interfere with plant growth, even able to increase the number of tillers per hill. The maximum number of tillers paddy SRI is 31.79 per hill, higher 79.90 % compared to Conventional paddy rice. The maximum number of tillers of Conventional paddy rice is 17,67 per hill. The grain yields of paddy SRI is 6.32 ton/ha, it is of 37.99 % higher than Conventional paddy rice. The grain yield of Conventional paddy rice is 4.58 ton/ha. Based on the results of field trials, can be recommended for further trials with measuring irrigation water.
Keywords: rowth, yield, paddy, SRI